Signifikasi Latihan Pranayama Terhadap Ketenangan Pikiran - Valentini, Ni Made Eva; Sumiati, Ni Ketut Rai (JURNAL YOGA DAN KESEHATAN, 2021)
Nowadays most people are not calm minded add to that the covid-19 pandemic. The impact of the covid-19 pandemic is such as excessive anxiety, depression, stress that causes the mind to be restless. This happens in all circles, whether from adolescents, adults, or even the elderly. Many factors affect this peace of mind. Various ways have been done by everyone, but that does not fully provide effectiveness to overcome this problem of peace of mind. Pranayama is booming nowadays by those who experience stress and disturbances in peace of mind along with the development of yoga asanas. With Pranayama it provides health and increased vitality, dissolves emotional tension and naturally calms the mind. The above statements reinforce that this pranayama can contribute to calm the mind of everyone. The formulation of the problems that form the basis of this research are: (1) Why is pranayama able to calm the mind ? (2) How does pranayama work so as to calm the mind? (3) What are the types of pranayama that can be done as a contribution to peace of mind? This data was obtained by library research techniques. Furthermore, data can be collected and analyzed with qualitative descriptive techniques. Based on the results of the study, it can be concluded that the significance of pranayama's practice of peace of mind is due to the presence of (1) The existence of respiratory and mind control that can strengthen the respiratory system, calm the nervous system that can calm the mind, (2) The way pranayama works starts from feeling relaxed, clothing which is used, as well as thepranayamaitself, (3) as well as the types of pranayama that contribute to calming the mind.